Nudes are Forever: Judicial Interpretations of Digital Technology's Impact on "Revenge Porn". Issue 1 (April 2019) - Dodge, Alexa
Abstract: In this article I explore judicial interpretations of the relationship between digital technology and non-consensual intimate image distribution (NCIID) (i.e., "revenge porn"). Drawing on my analysis of forty-nine Canadian cases of NCIID, I show that judicial interpretations of digital technology have important influences on how NCIID is understood and responded to in the law. I find that the majority of judges perceive digital technology as making NCIID easier to commit—with the simple "click of a mouse"—and as increasing the amount of harm caused by this act—as digital nude/sexual photos are seen as lasting "forever" and thus as resulting in ongoing and immeasurable harm to victims. These perceptions have substantive impacts on legal rationales and sentencing decisions, with the affordances of digital technology regularly being treated as justifying harsher sentences to denounce and deter this act. Résumé: En me fondant sur la littérature existante, dans cet article, j'explore la manière dont la relation entre la technologie numérique et la distribution non consensuelle d'images intimes (DNCII) (c.-à-d. pornodivulgation) a été comprise dans la jurisprudence canadienne. En m'appuyant sur mon analyse de quarante-neuf décisions canadiennes en matière de DNCII, je montre que les interprétations judiciaires de la technologie numérique influencent largement la façon dont la DNCII est comprise et traitée dans la loi. Je conclus que la majorité des juges perçoivent la technologie numérique comme facilitant la perpétration d'infractions de DNCII et également comme amplifiant les torts causés par ces actes. Ces perceptions ont des incidences substantielles sur les raisonnements juridiques et sur le processus de détermination de la peine, les moyens de la technologie numérique étant régulièrement utilisés afin de justifier des peines plus sévères, et ce, dans une optique de dissuasion et de dénonciation de cet acte.